Soft Paternalism, Merit Goods, and Normative Individualism - Gebhard Kirchgässner (Center for Economic Studies and ifo Institute (CESifo), 2014)
Paternalism is an attempt to influence individuals' decisions for their own benefit, even if there are no third parties involved. This seems to contradict normative individualism, which provides the general orientation to our modern democracies. Soft or libertarian paternalism accepts the necessity of paternalism due to the existence of behavioural anomalies, but intends to apply only such measures that do not restrict the decision leeway of individuals. Nevertheless, the same objections that can be raised against its strong version can also be raised against soft paternalism. On the other hand, as soon as we accept that human beings are able to reflect not only about their actions but also about the preferences guiding their actions, there is no longer a necessary contradiction between paternalism and normative individualism. As far as we know today, the possibilities to successfully apply soft paternalistic measures are rather limited. On the other hand, while some criticisms of it are justified, others largely overshoot the mark and seem to be at least partly ideologically motivated.
Keywords: H42; D63; D72; 330; libertarian paternalism; soft paternalism; merit goods; normative individualism; constitutional economics; democracy